Distribution and characteristics of inorganic nutrients in the surface microlayer and subsurface water of the Bohai and Yellow Seas. (15th September 2018) - Zhou, Li-Min; Sun, Yi; Zhang, Hong-Hai; Yang, Gui-Peng
Abstract: Concentrations and diurnal variations of inorganic nutrients (dissolved inorganic nitrogen (DIN), phosphate (PO4 -P) and silicate (SiO3 -Si)), as well as chlorophyll a (Chl-a) were determined in the subsurface water (SSW) and surface microlayer (SML) of the Bohai and Yellow Seas in summer 2015. The concentrations of DIN, SiO3 -Si and Chl-a (except for PO4 -P) in the SML were respectively correlated with their concentrations in the SSW, indicating that a major source of substances in the SML could be transported from the SSW. The enrichment factor (EF) was defined as the ratio of the concentration in the SML to that in the corresponding SSW. There was little difference in concentrations of PO4 -P between the SML and the SSW samples by nonparametric difference test (P > 0.05). DIN, SiO3 -Si and Chl-a (except for PO4 -P) were found to be enriched in the SML relative to the SSW, with average EFs of 2.45, 1.18 and 2.37, respectively. No connection was identified between nutrients EFs and wind speed for our entire data. DIN, SiO3 -Si, PO4 -P and Chl-a concentrations in the SSW and the SML exhibited strong diurnal variations at an anchor station. Highlights: Nutrients and Chl-a concentrations in the surface microlayer were determined. Nutrients and Chl-a in the surface microlayer showed more pronounced enrichment. Nutrients and Chl-a revealed obvious diurnal variations in the surface microlayer.